A novel application of stand-alone photovoltaic system in agriculture: solar-powered Microner sprayer. Issue 1 (2nd January 2017) - Karami Rad, Meysam; Omid, Mahmoud; Alimardani, Reza; Mousazadeh, Hosein
Abstract : In this paper, a stand-alone photovoltaic (SAPV) power supply system for Microner sprayer is identified and proposed. The designed system was composed of three main parts: sprayer, solar power supply and control system. Initially, the control board and data acquisition system were designed and simulated by the Proteus software and then implemented using an AVR microcontroller and tested via LabVIEW in the laboratory. Next, a prototype system was fabricated for evaluation purposes. A PV panel size of 88.5 cm 2, positioned horizontally above operator's head that generates 26.4 Wh/day was used as a solar energy source. A small 2 Ah (12 V) battery is installed in the system as a stabiliser. This sprayer can work seven to nine hours daily. It is calculated that the average loss of collected energy due to non-application of maximum power point tracker was approximately 25%.